PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN PENGUASAAN MATERI PENDIDIKAN AGAMA ISLAM - Ikhwansyah, Muhammad; Gunawan, Risal; Sulfiah, Sulfiah; Ridwan, Ridwan (DIDAKTIKA, 2022)
Application of the Discovery Learning Learning Model in Improving Mastery of Islamic Religious Education Materials for Class III at SD Islam Terpadu Asshiddiq Bone: First, Application of Learning Models in Improving Mastery of Islamic Education Materials, namely students who are less active can follow active students or form groups to solve problems. a problem together and can master the lessons in school, when well planned, learning models make learning more efficient, as well as with a variety of models taught to students so that students feel more comfortable when learning, and feedback occurs between students. And PAI teachers have implemented the Discovery Learning learning model so that all students can learn actively. Second, the Contribution of the Application of the Discovery Learning Learning Model in Improving Mastery of Islamic Education Materials for Third Grade Students at Asshiddiq Bone Islamic Elementary School has been running as expected, namely all students are actively involved in the learning process so that the classroom atmosphere becomes dynamic. And through the Discovery Learning Learning Model (discovery) providing teaching in learning, supervising or supervising student learning activities and habituation guidance for students to make discoveries so that they can make a positive contribution to students' abilities and achievements to build students' self-confidence both in terms of attitudes, knowledge and skills. skills. Third, the obstacles and solutions in implementing the Discovery Learning Learning Model (discovery) in Improving Mastery of Islamic Studies Materials for Third Students at the Asshiddiq Bone Islamic Elementary School, namely students with different characters, namely the character of students who are far from the average level and student competence. for example, in understanding the material given by the PAI teacher, and the imbalance between the number of students in one class and the media supply so that the conditioning of the class is difficult to control.